THE RELATIONSHIP BETWEEN DISCIPLINE AND EMOTIONAL INTELLIGENCE TOWARDS EMPLOYEE PERFORMANCE - Dian Rosa Linda; Puji Astuti; Satriya Wijaya (Universitas Airlangga, 2019)
Background: One of problems in an organization or company is poor performance of employees. For instance, they do not complete tasks or finish their job responsibilities on time. The preliminary data taken from one of companies in Surabaya showed that 184 employees did not come to work without any explanations, and 288 employees worked late.Aim: This study analyzed the relationships between discipline and emotional intelligence towards employee performance at the company.Method: The design of this research was analytical using a cross sectional approach. The population of this study was employees at Production and Maintenance Section of one company in Surabaya comprising of 155 people. Out of 155 employees, 89 respondents were taken as samples using a stratified random sampling technique. Then, the data were collected through a questionnaire and analyzed using Spearman’s rank correlation test with a significance level of α 0.05.Results: This study showed that most of the respondents were very highly disciplined (94.4%) and had a highly emotional intelligence (74.2%). Lastly, most of them perform satisfyingly (50.6%). The results of the analysis test with Spearman’s rank correlation yielded p-value of 0.002 <α 0.05. It means there was a correlation between discipline attitude and employee performance. The p-value 0.001 which was less than α-value of 0.05 showed that there was a correlation between emotional intelligence and employee performance.Conclusion: Discipline and emotional intelligence are prominent to determine employee performance at PT X. In order to improve the discipline and intelligence in the performance of the employees, the company should provide rewards based on employee’s achievements in the workplace. Key words: Emotional intelligence, Employee performance, Discipline.